2022
DOI: 10.1108/ilt-03-2022-0078
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of textured journal bearing operating with and without nanoparticles in the lubricant

Abstract: Purpose This study aims to investigate the performance improvement of journal bearing by applying the arc-shaped textures on various regions of bearing expressly full, second half and pressure increasing regions operating with and without nanoparticles in the lubricant. Design/methodology/approach The Reynolds equation is solved numerically by using the finite element method to obtain static performance parameters such as load-carrying capacity (LCC) and coefficient of friction (COF), which are then compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Comparative analysis of these texture shapes can provide the most effective shape and optimal operating parameters for enhancing the performance of hydrodynamic journal bearings. Figure 2(A) displays the circle, ellipse, rectangular, triangular, chevron and arc shapes and their corresponding geometric equations (a–f) as described by Manser et al (2019), Qiu et al (2013), Sharma et al (2020) and Byotra and Sharma (2022), which are all used in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of these texture shapes can provide the most effective shape and optimal operating parameters for enhancing the performance of hydrodynamic journal bearings. Figure 2(A) displays the circle, ellipse, rectangular, triangular, chevron and arc shapes and their corresponding geometric equations (a–f) as described by Manser et al (2019), Qiu et al (2013), Sharma et al (2020) and Byotra and Sharma (2022), which are all used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Existing literature also indicates that partial surface texturing can enhance the dynamic performance and stability of bearings. The goal of the study is to compare the various texture shapes, including the novel arc shape, an extended work of the same author's Byotra and Sharma (2022), in which the effect of arc shape textures on steady state performance of bearing being studied. In continuation/extension of previous work, the lubricant dynamic characteristics of novel arc and other shapes of textures are considered in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Partial texturing gives a higher load-carrying capacity than full texturing. Partial texturing between 180° to 360° gives better results in Researchers have employed FEM [57][58][59]70] for discretizing the governing equation in algebraic form. Table 2 presents the summary of articles involving isothermal investigations without considering cavitation effects using FEM.…”
Section: Numerical Investigations On the Performance Of Textured Jour...mentioning
confidence: 99%
“…Byotra and Sharma [31] developed a finite element model to analyze the performance improvement of a journal bearing by applying the arc-shaped textures on various regions of bearing operating with and without nanolubricants. They observed that the addition of Al 2 O 3 and CuO NPs increased the carrying-load capacity.…”
Section: Introductionmentioning
confidence: 99%